Scientific Criteria Applied To The Management Of Household Tasks: Paulette Bernège (1896-1973), And The ‘New, Liberated’ Bourgeois Woman. - Luque García, José Joaquín; Pinto Tortosa, Antonio Jesús (Tirant Humanidades, 2025)
In the context of the Great Depression and the beginning of the Second World War, gas companies tried to overcome the difficulties and the instability of the period, and at the same time they did all they could to confront electricity, which was becoming the main energy source, at least in lighting. In order to achieve both goals, they used publicity, among other tools. The French journal Gazette du Foyer, born in 1929 and aimed at middle-class and high-class French women, incarnated the aforementioned strategy. Though it included articles about fashion, domestic management, etc., it had been conceived as a marketing tool for promoting the use of gas in the country, focusing on women, so-called “demons of domesticity”. In the present chapter, we study Paulette Bernège’s contribution to the journal. French journalist specialized in domestic management, Bernège (1896-1973) collaborated with the Gazette du Foyer between 1932 and 1934. Influenced by F.W. Taylor’s ideas, she looked for the implementation of scientific principles to the performance of domestic tasks and household chores, so women carried them out more efficiently. Our goal is to analyze Bernège’s tips for organizing domestic tasks in a more productive way, describing some relevant examples of her articles in the journal section that she led, “Le ménage simplifié”.
Keywords: Mujeres - Situación social - S. XX; Trabajo doméstico; Gas - Industria - S. XX; Happiness; Homes; Women; Journals; Gas